Portable Bio-Devices: Design of electrochemical instruments from miniaturized to implantable devices - Colomer-Farrarons, Jordi; Miribel-Català, Pere Ll.; Rodríguez-Villarreal, A. Ivón; Samitier, Josep (IntechOpen, 2011)
None